Grain Boundary Passivation with Dion–Jacobson Phase Perovskites for High‐Performance Pb–Sn Mixed Narrow‐Bandgap Perovskite Solar Cells. Issue 4 (1st March 2021) - Zhang, Lei; Kang, Qiao; Song, Yanping; Chi, Dan; Huang, Shihua; He, Gang
Abstract : The mixed Pb–Sn perovskites have the ideal bandgap of ≈1.2 eV for photovoltaic application. However, the undesirable p‐doping introduced by Sn 2+ oxidation restrains the device's power conversion efficiency (PCE) and stability. Herein, an additive strategy with p‐phenyl dimethylammonium iodide (PhDMADI) is proposed, which has a bulky divalent organic cation and facilitates the formation of Dion–Jacobson phase‐based quasi‐2D perovskites at the grain boundaries. It is found that this unique 2D/3D bulk heterojunction structure is beneficial to suppress the oxidation of Sn 2+ and isolate the moisture and oxygen, resulting in a good stability of the solar cell. Moreover, the quasi‐2D perovskites can passivate defects effectively. The trap density of the perovskite film has decreased by one order of magnitude, thus the carrier lifetime is increased more than twice. These enhanced properties enable us to fabricate a device of 20.5% PCE with great stability. Abstract : An aromatic diammonium cation p‐phenyl dimethylammonium iodide is applied to facilitate the formation of Dion−Jacobson phase‐based quasi‐2D perovskites at the grain boundaries. Due to passivating defect and suppressing Sn 2+ oxidation, the trap density of the perovskite film decreases by one order of magnitude. Consequently, the Pb–Sn mixed narrow‐bandgap perovskite solar cells achieve an efficiency of 20.5% and exhibit great stability.